Anal Fissure : Symptoms, Diagnosis and Therapies - Wienert, Volker; Raulf, Franz; Mlitz, Horst (Springer International Publishing : Imprint: Springer, 2017)
This highly informative monograph offers a comprehensive and interdisciplinary reference for the management and treatment of the whole spectrum of painful tears in the anus and anal canal. Based upon a systematic review of all relevant papers on the topic starting from 1865, the book deals with the primary anal fissure, acute and chronic - with a new definition of the latter one provided - , and the secondary anal fissure in every detail, particularly its medical history , etiology , signs and symptoms , medical findings , therapy and its evaluation, differential diagnosis. It also covers all available evidence based therapeutic strategies. This book will appeal to a wide readership, from proctologists and surgeons through gynecologists, to urologists, dermatologists and gastroenterologists.
Keywords: Medicine.; Dermatology.; Gynecology.; Gastroenterology.; Nursing.; Rectum -- Surgery.; Urology.; elektronické knihy; electronic books